Гость полнолуния: [роман] / Ярослава Лазарева - Лазарева Ярослава (Пленники сумерек, 2010)
Экземпляры: аб. (2012) / Инвентарный номер: 48742 / Цена: / Сис.шифр: 84Р6 / Авт.знак: Л 17 / ББК: 84(2Рос=Рус)6